Persepsi Guru Terhadap Self Efficacy - Sulastika, Rika; Juniarti, Aristia (Yayasan Sembilan Pemuda Indonesia, 2025)
This research aims to reveal the perceptions of teachers at SMA Negeri 2 Tanah Abang regarding their self-efficacy in carrying out teaching tasks. The novelty of this research lies in the effort to understand more deeply the factors that influence teachers' self-confidence in carrying out their profession, as well as identifying the strategies they use to increase self-efficacy. This research uses a qualitative approach with in-depth interviews. The research sample consisted of 5 teachers at SMA Negeri 2 Tanah Abang. The data obtained was then analyzed using thematic analysis. The research results show that teachers have a fairly high level of self-efficacy. The factors that influence teacher self-efficacy are teaching experience, support from the school environment, and professional development. The contribution of this research lies in the development of theory. This research can contribute to the development of self-efficacy theory in the educational context, especially at the high school level. Educational practices resulting from research can be the basis for schools to design more effective professional development programs and create supportive work environments for teachers. Further research, namely this research, can become the basis for further research with a wider scope or using different methods.